ANALISIS DAYA SERAP DAN DAYA TEKAN BATAKO PRES, TERHADAP INTERAKSI FAKTOR PEKERJA, FAKTOR KOMPOSISI AIR, DAN FAKTOR KOMPOSISI KAPUR-PASIR - Sutoni, Akhmad; Gunawan, Dani (Jurnal Media Teknik dan Sistem Industri, 2018)
Abstract— The need for building materials in recent decades has increased. One of them is the need of "Prescription Batako". This can happen along with the increasing of infrastructure development in society. As a result, the challenge of reaching market demand is also greater. This condition demands each Preservation Batako company to provide maximum product Quality. The purpose of this research is to know what factors affect the results of Prescription Batako products. The method used is a Design Experiment using Factorial Factor Three Factor. The three factors are Worker factor, water composition factor, and with sand-lime composition factor. Data processing is assisted by SPSS software. Influence which is analyzed by three factors are absorption and compressive power. These three factors have a significant effect on absorption and compressive power.Keywords— Design Experiment; Factorial Three Factor Kata kunci : Design Experiment, Faktorial Tiga Faktor